2006
DOI: 10.1016/j.euje.2005.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Stress echocardiography is superior to exercise ECG in the risk stratification of patients presenting with acute chest pain with negative Troponin

Abstract: Despite negative cardiac Troponin, 12% of patients with acute chest pain had significant CAD. SE is superior to ExECG in discriminating between those patients with a low and intermediate risk of CAD and correctly identified patients with significant CAD, as well as conferring an excellent prognosis in those considered low risk. SE significantly reduces the requirement for further tests to diagnose CAD compared to ExECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
0
20
0
2
Order By: Relevance
“…Certainly this and other studies have shown that the rate of positive tests is very low,4 5 8–10 16–21 small proportions would therefore be considered ‘at-risk’. Also there are small proportions of false-positives (with consequent unnecessary exposure of some patients to the risks of invasive testing) and false-negatives (giving a false sense of security to those with negative results), although this is inherent with a test that intends to stratify risk rather than give a definitive result.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Certainly this and other studies have shown that the rate of positive tests is very low,4 5 8–10 16–21 small proportions would therefore be considered ‘at-risk’. Also there are small proportions of false-positives (with consequent unnecessary exposure of some patients to the risks of invasive testing) and false-negatives (giving a false sense of security to those with negative results), although this is inherent with a test that intends to stratify risk rather than give a definitive result.…”
Section: Discussionmentioning
confidence: 67%
“…Also there are small proportions of false-positives (with consequent unnecessary exposure of some patients to the risks of invasive testing) and false-negatives (giving a false sense of security to those with negative results), although this is inherent with a test that intends to stratify risk rather than give a definitive result. In addition, proportions of patients with non-diagnostic results are high4 5 9 17–23 (again risking unnecessary exposure to invasive testing).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared to exercise ECG, dobutamine stress echocardiography was found to be more cost effective: the mean length of stay in the hospital was lower; and no event occurred in a 2 month follow-up in patients with a normal dobutamine test, whereas the event rate was 11% in patients with normal exercise ECG 7. Several studies combining patients submitted to exercise echocardiography or dobutamine stress echocardiography have also demonstrated good risk stratification, especially through a high negative predictive value 8 9…”
Section: Acute Chest Pain: Suspicion Of Acute Coronary Syndromementioning
confidence: 99%
“…Dieser Vorteil ist allerdings mit dem Nachteil einer fehlenden Bildgebung auf der höchsten Belastungsstufe verbunden, die mittels Fahrradergometrie kontinuierlich erfolgen kann. [19]. Dieser Vorteil in der Sensitivität spricht klar für den Einsatz der modernen Bildgebung in der Ischämie-diagnostik.…”
Section: Ischämiediagnostikunclassified